Acceptability of crackers (‘Keropok’) with fish protein hydrolysate - Yu, S. Y.; Tan, L. K. (Institute of Food Science and Technology, 1990)
Proteins from Oreochromis mossambicus, a freshwater fish, were hydrolysed, using alkalase 0.61, to produce a soluble, spray-dried hydrolysate. The hydrolysis was carried out at 50°C, using a ratio of one part water and one part fish mince, an enzyme:substrate ratio of 1:50 at pH 8.0. Reaction was terminated by heating to 90°C for 20min. After neutralization, the soluble fraction obtained after centrifugation was spray dried in a mini spray-drier, at an air inlet temperature of 170°C and a feed rate of 41−1. The spray-dried hydrolysate was incorporated into crackers which are fried before eating. Ten per cent hydrolysate was found to give maximum linear expansion. Sensory evaluation with 20 experienced assessors showed that in terms of appearance, crispiness and colour, crackers with hydrolysate had the highest scores, compared to crackers made with O. mossambicus and Sciaena sp. (Jewfish). There were no significant differences in overall acceptability in all three samples. Crackers with hydrolysate also had the highest nitrogen content.